Weighted window and class-based weighted window methods for per-station TCP fairness in IEEE 802.11 WLANs. - Othman, Mohamed; Seyedzadegan, Mojtaba (Hindawi Publishing Corporation, 2010)
TCP unfairness problem in access networks using the 802.11 has been studied by many researchers. Their solutions required that the existing MAC protocol be modified. However, since they did not consider the case when each wireless node has a different number of flows, they cannot provide fairness among wireless nodes having different numbers of flow in both directions. In order to resolve this problem, Weighted Window and Class-Based Weighted Window methods are proposed. In the Weighted Window method, each wireless node can control the rate of TCP flows based on TCP window size. By applying this method, per-station fairness can be achieved, regardless of the number and direction of flows in each wireless node. Furthermore, to improve and to provide fair bandwidth allocation in the Weighted Window method when the users have different requirements, the Class-Based Weighted Window method is proposed. Therefore, for wireless nodes with different requirements, fair allocation bandwidth between wireless nodes in the same class of bandwidth is achieved.